The missed diagnosis of aortic dissection in patients with acute myocardial infarction: a disastrous event - Wang, Di; Zhang, Li-Li; Wang, Zhi-Yan; Zhang, Zhen-Yu; Wang, Yi (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
We present a case of aortic dissection (AD) accompanied by acute myocardial infarction (AMI). For patients with AMI, the missed diagnosis of AD could be catastrophic. Therefore, we strongly recommend that portable echocardiography should be routinely available in the ambulance. Moreover, multicenter studies concerning the cost-benefit ratio of portable echocardiography routinely available in the ambulance should urgently be considered.